2015
DOI: 10.1016/j.ejmech.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan dendrimers that inhibit HIV replication, prevent virus entry and bind to the HIV envelope glycoproteins gp120 and gp41

Abstract: Dendrimers containing from 9 to 18 tryptophan residues at the peryphery have been efficiently synthesized and tested against HIV replication. These compounds inhibit an early step of the replicative cycle of HIV, presumably virus entry into its target cell. Our data suggest that HIV inhibition can be achieved by the preferred interaction of the compounds herein described with glycoproteins gp120 and gp41 of the HIV envelope preventing interaction between HIV and the (co)receptors present on the host cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 47 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…Study of the structure-activity relationship (SAR) led to the following conclusions: (i) the absence of Trp on the periphery is detrimental for anti-EV71 activity ("nude acids" 10 and 11 were inactive at EC 50 s of Ͼ98 and Ͼ48 M, respectively); (ii) multivalent presentation of Trp is important for anti-EV71 activity (compound 9, with only three Trp residues, is inactive, while its respective superior analog, 5, with nine Trp residues is active); (iii) the presence of 9 or 12 Trp residues on the periphery is sufficient for anti-EV71 activity (compound 6, with 12 Trp residues, was more active than compounds 7 and 8, with 15 and 18 Trp residues, respectively); and (iv) the flexibility of the central scaffold does not appear to have a pronounced impact on antiviral activity (compounds 1 and 2, with triethylbenzene and benzene rigid cores, respectively, showed activity similar to that of compound 3, with a more flexible cyclohexane core). Interestingly, the SAR that is described here for EV71 is very similar to that previously reported for HIV (13).…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Study of the structure-activity relationship (SAR) led to the following conclusions: (i) the absence of Trp on the periphery is detrimental for anti-EV71 activity ("nude acids" 10 and 11 were inactive at EC 50 s of Ͼ98 and Ͼ48 M, respectively); (ii) multivalent presentation of Trp is important for anti-EV71 activity (compound 9, with only three Trp residues, is inactive, while its respective superior analog, 5, with nine Trp residues is active); (iii) the presence of 9 or 12 Trp residues on the periphery is sufficient for anti-EV71 activity (compound 6, with 12 Trp residues, was more active than compounds 7 and 8, with 15 and 18 Trp residues, respectively); and (iv) the flexibility of the central scaffold does not appear to have a pronounced impact on antiviral activity (compounds 1 and 2, with triethylbenzene and benzene rigid cores, respectively, showed activity similar to that of compound 3, with a more flexible cyclohexane core). Interestingly, the SAR that is described here for EV71 is very similar to that previously reported for HIV (13).…”
supporting
confidence: 86%
“…1, compounds 1 to 11) that are linked to the dendrimer branches through an amino group. These compounds were shown to inhibit an early step in the replication cycle of HIV by interacting with glycoproteins gp120 and gp41 of the HIV envelope (13). Further exploration in virus-cell-based assays for broad-spectrum antiviral activity against other viruses (herpes simplex viruses 1 and 2, vaccinia virus, varicella-zoster virus, vesicular stomatitis virus, respiratory syncytial virus, reovirus 1, Sindbis virus, Punta Toro virus, cytomegalovirus, influenza virus A [subtypes H1N1 and H3N2], influenza virus B, feline coronavirus, and feline herpes virus) did not reveal any inhibitory activity, except when evaluated against EV71, a virus whose structure and mechanism of replication are completely different than those of HIV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of the studied compounds to gp120 and gp41 was proven by surface plasmon resonance studies. The compound with 15 tryptophans on the periphery had the best anti‐HIV‐1 activity with EC 50 of 2.2 μ m …”
Section: Hiv‐1 Entry Inhibitorsmentioning
confidence: 99%
“…We have previously reported that dendrimer derivatives, with peripheral tryptophan (Trp) residues and trivalent aliphatic branched arms, exemplified by dendrimer 1 (Fig. 1), inhibit an early step in the replicative cycle of HIV by interacting with the gp120 and gp41 glycoproteins of the HIV envelope (Rivero-Buceta, 2015). Due to the current interest in HIV entry inhibitors associated with gp120 binding, our https://doi.org/10.1016/j.antiviral.2019.06.006 Received 24 October 2018; Received in revised form 31 May 2019; Accepted 3 June 2019 Trp dendrimers are attractive candidates for further development.…”
mentioning
confidence: 99%